Comprehensive enhancement in overall properties of MWCNTs-COOH/epoxy composites by microwave: An efficient approach to strengthen interfacial bonding via localized superheating effect. (1st October 2019) - Liu, Xin; Luo, Jintao; Fan, Jinfeng; Lin, Song; Jia, Liying; Jia, Xiaolong; Cai, Qing; Yang, Xiaoping
Abstract: By applying microwave (MW), strengthening effect of carboxylated MWCNTs (MWCNTs-COOH) on mechanical, thermal and electrical properties of epoxy (EP)-based composites was systematically evaluated. The localized superheating effect under MW contributed much in improving the dispersibility and dispersion stability of MWCNTs-COOH in EP matrix. MWCNTs-COOH/EP composites E α via MW curing (MWC) showed the inside-out solidification mode associated with lower activation energy ( α ) over the range of cure (). An unique feature of MW was to enhance stress transfer and the formation of uniform MWCNT conducting networks, thus leading to a comprehensive enhancement in overall properties of resulting composites.